Comparison of the vertical distribution of chlorpyrifos and diazinon in andic soils columns (Revista de Investigaciones Universidad del Quindío, 2013)
In this work the vertical distribution process of the organophosphorus pesticides chlorpyrifos and diazinon with the vertical distribution of some physical and chemical properties of Cauca department andic soil for the potatoes growing is evidenced and compared, in order to contribute to the understanding of the subsurface leaching process of these compounds in soils that contain high organic carbon content (CO) between 8.4 and 19.5%, clay of 15-22%, humidity(0.3 bar) between 60 and 68% porosity 77 - 83%, pH between 4.7-5.0, high phosphate retention (92-98%) and ratio of Al + ½ Fe between 2.6-3.5%. The properties and classification were measured according Key Soil Taxonomy. For plaguicide extraction, 1 g of soil was taken every 5 cm, 5.0 mL of acetone was added, was subjected to ultrasonic and centrifugation, filtration and injection of 0.2 μL by GC-ECD. Using methyl parathion as internal standard. It is noted that the soil columns in the distribution of both pesticides after a rain event reaches 30 cm of profile, maintaining a proportional distribution in all columns of soil to 80% for chlorpyrifos in the first 10 cm and 60 % for diazinon. It highlights the complexity recorded in the vertical distribution of pesticides in the soil columns up to 30 cm in correspondence with the distribution complexity of variables CO, clay, humidity, porosity and pH measured.
Keywords: Lixiviación; propiedades ándicas; plaguicidas; distribución vertical; clorpirifos; diazinon